Feasibility and performance of TiCN-based patch antennas for microwave antenna applications - Mohamad Ashry, Jusoh; Nor Izaty Eisafyra, Pamin; Nur Iffah Zulaikha, Azman; Rodziah, Nazlan; Siti Aisah, Harun (Springer, 2024)
Titanium Carbonitride (TiCN) ofers a wide range of advantages due to its distinctive characteristics. This study investigates the feasibility of utilizing TiCN for microwave antenna applications. This paper describes the whole process, starting with the synthesizing of materials until the fabricating and testing of TiCN-based patch antenna. The TiCN paste was prepared using a hydrothermal method, and its crystallinity was analyzed using X-ray difraction. The functional group of the TiCN paste was determined through FTIR analysis, while the morphology of the paste was examined using FESEM/EDX. The TiCN paste was applied onto an RT duroid 5880 substrate using screen-printing techniques, resulting in a strong bond between the paste and substrate as confrmed by the adhesion test. The antenna’s performance was evaluated using the Vector Network Analyzer, revealing two resonant frequencies at 9.08 GHz and 16.96 GHz. The return loss values for these frequencies are − 12.10 dB and − 16.25 dB, respectively. A calculated bandwidth of 950 MHz at − 10.00 dB was found for resonant frequency of 16.96 GHz. This performance indicates the promise of TiCN-based patch antennas for wireless communication technologies.